Intermittent negative pressure therapy in patients with no-option chronic limb-threatening ischemia: original communication - Yagshyyev, Shatlyk; Hausmann, Phillip; Li, Yi; Kempf, Julius; Zetzmann, Katharina; Dessi, Katia; Moosmann, Oxana; Almasi-Sperling, Veronika; Meyer, Alexander; Gerken, Andreas; Lang, Werner; Rother, Ulrich (Vasa, 2023)
Summary:Background: Aim of this study was to assess the influence of intermitted negative pressure (INP) therapy on the foot microcirculation in patients with no-option CLTI. Patients and methods: CLTI patients defined as no option for revascularization on the basis of an interdisciplinary vascular board decision (interventional radiology, vascular surgery) were included in this study. INP therapy was performed at home. Therapy regime was: 1 hour twice daily. Follow-up was after 6 weeks and 3 months. Microcirculation measurement was performed by laser Doppler flowmetry and white light spectrometry (oxygen to see, O2CTM). Following parameters were evaluated: oxygen saturation (sO2 in%), relative hemoglobin (rHb) and flow (in arbitrary units A.U.). Additionally the clinical outcome of the patients was assessed. Results: From September 2020 to June 2022, 228 patients were screened. In total 19 patients (13 men, 6 women, mean age was 73.95 years) were included. 6 weeks after INP therapy the microcirculation showed a significant improvement for the parameter sO2 (%) (p=0.004). After 3 months a non-significant decrease compared to 6 weeks follow-up was seen for the parameter sO2; however, the perfusion was still improved compared to baseline measurement. With regard to the microperfusion values flow (AU) and hemoglobin (AU), the changes were not significant. Clinically, the patients reported a significant reduction of rest pain after therapy (p=0.005). Conclusions: INP therapy in no-option CLTI patients showed a significant improvement of the skin perfusion after 6 weeks. Therefore, INP therapy might have therapeutic potential in these critical ill patients.
Online veröffentlicht: 17. Oktober 2023
Gesehen am 14.10.2024